2016
DOI: 10.1016/j.cej.2016.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Configuration optimization of UV reactors for water disinfection with computational fluid dynamics: Feasibility of using particle minimum UV dose as a performance indicator

Abstract: h i g h l i g h t sD min was used as a performance indicator for UV reactor configuration optimization. D min proved to be a qualified alternative to RED for UV reactor optimal design. Reactor with a well-mixed flow dispersed by lamp array had the best performance. Disinfection capability of the optimally designed UV reactor was elevated by 47À100%. t r a c tComputational fluid dynamics is a powerful tool for ultraviolet (UV) reactor performance evaluation, since it allows the reactor configuration optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Parameter FR aa : area-averaged FR (mW cm À2 ); FR max : maximum FR (mW cm À2 ); FR min : minimum FR (mW cm À2 ); and RSD: relative standard deviation. minimum fluence (F min ), which plays a determinant role in the REF (Li et al, 2016), would most probably be found with particles traveling in the near-wall region. Because the FR va increment was a net result of the FR increase in the near-wall region subtracting the FR decrease in the near-lamp region, the degree of increase in the F min was slightly greater than that in the FR va .…”
Section: Effect Of Inner-wall Reflection On Refmentioning
confidence: 99%
“…Parameter FR aa : area-averaged FR (mW cm À2 ); FR max : maximum FR (mW cm À2 ); FR min : minimum FR (mW cm À2 ); and RSD: relative standard deviation. minimum fluence (F min ), which plays a determinant role in the REF (Li et al, 2016), would most probably be found with particles traveling in the near-wall region. Because the FR va increment was a net result of the FR increase in the near-wall region subtracting the FR decrease in the near-lamp region, the degree of increase in the F min was slightly greater than that in the FR va .…”
Section: Effect Of Inner-wall Reflection On Refmentioning
confidence: 99%
“…Various methods have been developed based on the two mentioned routes. For example, a pipe-type reactor with a small diameter has been explored for maximization of ultraviolet light intensity [17][18][19]22]. However, this method has the disadvantage that the long contact time (residence time) required for the reaction can be only obtained by designing a long reaction pipe, which is normally limited by actual situations.…”
Section: Comparison Of Experimental and Simulation Resultsmentioning
confidence: 99%
“…The RAVR integrated the flow characteristics of a continuous-flow stirred-tank reactor (CSTR) and a plug flow reactor (PFR). As mentioned in Section 1, the RAVR is an economical reactor with good mixing function compared with long tubular reactors [17][18][19] or reactors with internal baffles [3,20,21]. The rotating flow along the VUV lamp in a RAVR reactor plays the role of mixing and extending the fluid-retention time, and there is thus no dead zone in a RAVR reactor.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Therefore, in this work we researched the effect of the reaction mixture position about light source and the reaction time on the performance of a photograft polymerization. The surface of PP films was modified by using a UV-induced graft polymerization of acrylic acid (AA), selected as a reaction model. ,, It is known that the distance between the light source and reaction mixture is a crucial variable for this kind of reaction . In order to monitor the changes of lamp light intensity against the variables mentioned above, we used a photoconductive cell of CdS as a light sensor. Benzophenone was used as a radical photoinitiator agent in an aqueous reaction mixture containing AA .…”
Section: Introductionmentioning
confidence: 99%